2009
DOI: 10.1016/j.biomaterials.2009.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release of antibiotic from poly(2-hydroxyethyl methacrylate) to prevent blinding infections after cataract surgery

Abstract: Intraocular lens implantation after opacified natural lens removal is the primary treatment for cataracts in developed countries. Cataract surgery is generally considered safe, but entails significant risks in countries where sophisticated sterile operating theaters are not widely available. Post-operative infection (endophthalmitis) is a potential blinding complication. Infection often results from bacterial colonization of the new lens implant and subsequent antibiotic-tolerant biofilm formation. To combat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 21 publications
1
45
0
1
Order By: Relevance
“…However, similar studies have shown that no additional alkyl groups were observed on the surface of samples reacted with isocyanate for longer than 30 minutes. 21 Samples coated longer than 30 minutes appeared to swell and eventually degraded in the isocyanate-THF solution. Degradation was more apparent in more hydrophobic samples, i.e., samples with more HPMA component.…”
Section: Resultsmentioning
confidence: 99%
“…However, similar studies have shown that no additional alkyl groups were observed on the surface of samples reacted with isocyanate for longer than 30 minutes. 21 Samples coated longer than 30 minutes appeared to swell and eventually degraded in the isocyanate-THF solution. Degradation was more apparent in more hydrophobic samples, i.e., samples with more HPMA component.…”
Section: Resultsmentioning
confidence: 99%
“…18 The most common adverse event of antibiotics (for example, macrolides) is gastrointestinal (GI) stimulus that appears to be dose related; therefore, bypassing the absorption site in the upper GI tract is necessary especially in sustained-release preparations with larger dosage. It is known that variations of pH occur at GI tract, and hence application the pH-responsive carriers may be a solution.…”
Section: Significant and Sustained Improvement In Lung Function And Rmentioning
confidence: 99%
“…[53] Based on previous studies on the same ortho ester structure, [54,55] the hydrolysis of the PEYM pendant chains should lead to the production of hydroxybutyric acid, ethanol, and poly(2-hydroxyethyl methacrylate), which is a hydrophilic polymer with excellent biocompatibility [56] and is widely used as drug carriers in the forms of microspheres, hydrogels, and nanogels, due to their strong intramolecular/intermolecular hydrogen bonding. [57,58] The kinetics of the PEYM side-chain hydrolysis can be quantified based on the released amount of hydrolyzed product (ethanol) and was determined using an enzyme-based assay. The time/pH-dependence of hydrolysis is shown quantitatively in Figure 3.…”
Section: Polymermentioning
confidence: 99%